Monitoring Pharmaceuticals and Personal Care Products in Drinking Water Samples by the LC-MS/MS Method to Estimate Their Potential Health Risk - Molnarova, Lucia; Halesova, Tatana; Vaclavikova, Marta; Bosakova, Zuzana (Molecules, 2023)
(1) The occurrence and accumulation of pharmaceuticals and personal care products in the environment are recognized scientific concerns. Many of these compounds are disposed of in an unchanged or metabolized form through sewage systems and wastewater treatment plants (WWTP). WWTP processes do not completely eliminate all active substances or their metabolites. Therefore, they systematically leach into the water system and are increasingly contaminating ground, surface, and drinking water, representing a health risk largely ignored by legislative bodies. Especially during the COVID-19 pandemic, a significantly larger amount of medicines and protective products were consumed. It is therefore likely that contamination of water sources has increased, and in the case of groundwater with a delayed effect. As a result, it is necessary to develop an accurate, rapid, and easily available method applicable to routine screening analyses of potable water to monitor and estimate their potential health risk. (2) A multi-residue UHPLC-MS/MS analytical method designed for the identification of 52 pharmaceutical products was developed and used to monitor their presence in drinking water. (3) The optimized method achieved good validation parameters, with recovery of 70-120% of most analytes and repeatability achieving results within 20%. In real samples of drinking water, at least one analyte above the limit of determination was detected in each of the 15 tap water and groundwater samples analyzed. (4) These findings highlight the need for legislation to address pharmaceutical contamination in the environment.
Keywords: chemické látky znečišťující vodu; Water Pollutants, Chemical; pitná voda; monitorování životního prostředí; Tandem Mass Spectrometry; lidé; Chromatography, Liquid; Pharmaceutical Preparations; COVID-19; léčivé přípravky; pandemie; tandemová hmotnostní spektrometrie; Drinking Water; Environmental Monitoring; Cosmetics; kosmetické přípravky; Pandemics; chromatografie kapalinová; Humans